Performance and emission assessment of diesel–biodiesel–ethanol/bioethanol blend as a fuel in diesel engines: A review. (August 2015) - Shahir, S.A.; Masjuki, H.H.; Kalam, M.A.; Imran, A.; Ashraful, A.M.
Abstract: The aim of this review is to study the opportunities and prospects of introducing diesel–biodiesel–ethanol/bioethanol blend as fuel in the existing diesel engines. The study is based on the engine emissions and its performance. The energy policies and the ever growing energy demand of the world, require an alternative to fossil fuels. In this quest, the diesel–ethanol blend or the diesohol blend might be a good option. But this blend possesses stability problem as well as inferior physicochemical properties when compared to diesel fuel and needs additives to remain stable. When biodiesel is used as an additive in this diesohol blend, it improves the physicochemical properties of the ternary blend, engine performance and also increases the renewable portion of the blend. First the engine performance and emissions data found by using diesel–biodiesel–ethanol/bioethanol ternary blends are accumulated. Then the results of the scientists and investigators are discussed to evaluate its potential as an alternative to fossil diesel fuel. The physicochemical properties of ternary blends are found to be almost similar to the diesel fuel. These ternary blends significantly reduce the PM (particulate matter) emissions from the diesel engine but the emissions of NO x (nitrogen oxides), soot and smoke, HC (hydrocarbon), CO (carbon monoxide), CO2 (carbon dioxide) and the carbonyl compounds depend on the operating conditions of the engine and remain almost similar to the diesel fuel exhaust.